Studi pengaruh temperatur dan konsentrasi ion klorida terhadap korosi sumuran dan Critical Pitting Temperature material UNS S31603 - Bambang Widyanto; Catia Julie Aulia (Jurnal Metalurgi dan Material Indonesia, 2018)
This experiment simulates a pitting corrosion on UNS S31603 with a variation of temperature and concentration of chloride ions through immersion testing based on ASTM G48 Method E to determine Critical Pitting Temperature. Solution containing FeCl3.6H2O, HCl 37%, and reagent water was used. The tests carried out at temperatures 10oC, 20oC, 25oC, 30oC, and 35oC with variation of chloride ion concentration; 2M; 2.25M; and 2.5M. The immersion test was performed for 24 hours for each specimen with stirring speed 300 rpm. The test results show that the temperature and concentration of chloride ions influence the formation of pitting on UNS S31603 specimens. An increment in temperature will accelerate the reaction rate so the number of pit increases. An increment in the concentration of chloride ions accelerate the dissolution of passive layer on the specimen’s surface, beside increase of the number of pits and increase of depth, there is also other phenomenon where the pits gradually interconnected each other due to the adjacent pits position. The concentration of chloride ions would affect the Critical Pitting Temperature.